Sequential Oxygenation Index and Organ Dysfunction Assessment within the First 3 Days of Mechanical Ventilation Predict the Outcome of Adult Patients with Severe Acute Respiratory Failure. (18th February 2013) - Kao, Hsu-Ching; Lai, Ting-Yu; Hung, Heui-Ling; Chen, Yu-Mu; Chou, Po-An; Wang, Chin-Chou; Lin, Meng-Chih; Fang, Wen-Feng
Abstract : Objective . To determine early predictors of outcomes of adult patients with severe acute respiratory failure. Method . 100 consecutive adult patients with severe acute respiratory failure were evaluated in this retrospective study. Data including comorbidities, Sequential Organ Failure Assessment (SOFA) score, Acute Physiological Assessment and Chronic Health Evaluation II (APACHE II) score, PaO2, FiO2, PaO2 /FiO2, PEEP, mean airway pressure (mPaw), and oxygenation index (OI) on the 1st and the 3rd day of mechanical ventilation, and change in OI within 3 days were recorded. Primary outcome was hospital mortality; secondary outcome measure was ventilator weaning failure. Results . 38 out of 100 (38%) patients died within the study period. 48 patients (48%) failed to wean from ventilator. Multivariate analysis showed day 3 OI (P = 0.004 ) and SOFA (P = 0.02 ) score were independent predictors of hospital mortality. Preexisting cerebrovascular accident (CVA) (P = 0.002 ) was the predictor of weaning failure. Results from Kaplan-Meier method demonstrated that higher day 3 OI was associated with shorter survival time (log-Rank test, P < 0.001 ). Conclusion . Early OI (within 3 days) and SOFA score were predictors of mortality in severe acute respiratory failure. In the future, prospective studies measuring serial OIs in a larger scale of study cohort is required to further consolidate our findings.